Combining experimental strategies for successful target deconvolution. Issue 11 (November 2020) - Wilkinson, Isabel V.L.; Terstappen, Georg C.; Russell, Angela J.
Highlights: Target deconvolution can enhance pharmaceutical R&D productivity. A combination of approaches is usually required for successful target deconvolution. Target validation should include direct binding, target engagement and functional studies. Target ID methods usually focus on proteins, overlooking RNA, DNA, lipid and metal ion targets. Abstract : Investment in phenotypic drug discovery has led to increased demand for rapid and robust target deconvolution to aid successful drug development. Although methods for target identification and mechanism of action (MoA) discovery are flourishing, they typically lead to lists of putative targets. Validating which target(s) are involved in the therapeutic mechanism of a compound poses a significant challenge, requiring direct binding, target engagement, and functional studies in relevant physiological contexts. A combination of orthogonal approaches can allow target identification beyond the proteome as well as aid prioritisation for resource-intensive target validation studies.